Faktor Determinan Kejadian Stunting pada Balita Usia 24-59 Bulan - Fatihunnajah, Muhammad Fadlil; Budiono, Irwan (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Stunting is still one of the most common and unresolved nutritional problems, in Margasari District stunting cases increased in August 2020. The purpose of this study was to analyze the factors associated with stunting in toddlers aged 24-59 months in the working area of the Margasari Health Center. Methods: This study uses an observational analytic quantitative research type with a case control design. Sampling using non-random sampling technique with purposive sampling method and a sample of 98 toddlers consisting of 49 children in the case and control groups. Data analysis consisted of chi-square test and Odds Ratio. This study uses secondary data from the mother's KIA book and primary data through interviews. Results: The results of the analysis showed that the factors that had a significant relationship with the incidence of stunting in toddlers were family income (P = 0.026; OR = 2.729), mother's educational status (p = 0.037; OR = 2.658), exclusive breastfeeding (p = 0.043; OR = 2.510 ), complementary foods (p=0.002; OR=4,240), and energy intake (p=0.004; OR=5,110). While the factors that were not significantly related were maternal employment status (p = 0.492; OR = 1.524), diarrhea (p = 0.074; OR 3.932), immunization status (p = 1000; OR = 0.652), and low birth weight (p = 0.678; OR = 0.479). Conclusion: This study suggests to the government to create an effective stunting prevention program, besides that the community is expected to increase knowledge about nutrition before deciding to have children.